Enhanced nano composite catalyst based on MOFs (Metal-Organic Frameworks) material, preparation method and application
Through nanocomposite catalysts based on MOFs materials, Cu/ZIF and CaS2O3 are used to catalyze the production of OH in the tumor microenvironment, the problems of low efficiency and high toxicity of tumor treatment in the prior art are solved, and efficient tumor cell killing and Improved biocompatibility.
Patent Information
- Application Number
- CN202411709183.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-27
AI Technical Summary
Existing tumor treatment methods such as chemotherapy and radiotherapy have systemic toxicity, locality and drug resistance problems, and the H2O2 content at the tumor site is not sufficient to produce enough OH to effectively kill cancer cells.
Using a reinforced nanocomposite catalyst based on MOFs materials, Cu/ZIF is coordinated with 2-methylimidazole by copper ions and zinc ions, and CaS2O3 is obtained by combining thiosulfate and calcium salt, and wrapped with polyethylene glycol PEG. Nanocomposite catalysts forming mesoporous structures are used to catalyze H2O2 production·OH in the tumor microenvironment.
The nanocomposite catalyst maintains a high degradation rate within the pH range of 3.0 to 10.0, which can generate OH to change cell membrane permeability, prevent Ca2+ transport, lead to calcium overload and synergistic effects of tumor cells, and improve the killing efficiency of tumor cells. And improve biocompatibility through PEG packaging.
Smart Images

Figure CN119185242A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material preparation, and in particular to an enhanced nano composite catalyst based on MOFs material, a preparation method and application thereof. Background Art
[0002] At present, the traditional medical treatments for tumors are mainly chemotherapy, radiotherapy and surgery. Chemotherapy is prone to cause systemic toxicity and drug resistance, radiotherapy can only treat local tumors, and surgical resection can only be used for early-stage cancer patients, and there is a risk of recurrence. Therefore, it is necessary to find a method with low risk and high efficacy.
[0003] Chemodynamic therapy (CDT) uses transition metal nanomaterials as catalysts to respond in the micro-acidic environment (TME) unique to tumors. Fenton reaction or Fenton-like reaction is the key step of CDT. In these reactions, transition metal ions catalyze the decomposition of H2O2 to produce highly active reactive oxygen species (ROS). ROS are strong oxidants that can damage cell membranes, proteins, and DNA, leading to tumor cell death. Although the H2O2 content and acidity in the tumor site are higher than those in normal tissues, it may still not be enough to produce enough ·OH to effectively kill cancer cells. However, current chemotherapy drugs are not very effective. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides an enhanced nano composite catalyst based on MOFs material, a preparation method and application thereof.
[0005] The technical solution adopted by the present invention is: A method for preparing an enhanced nanocomposite catalyst based on MOFs material comprises the following steps: Step 1: Copper ions and zinc ions are used as metal sources to coordinate with 2-methylimidazole, and Cu / ZIF is obtained by centrifugation, washing, and freeze-drying; Step 2: Thiosulfate and calcium salt undergo replacement reaction to obtain CaS2O3; Step 3: Fully mix the Cu / ZIF solution obtained in step 1 and the CaS2O3 solution obtained in step 2, add polyethylene glycol PEG and fully mix and react to obtain the desired nanocomposite catalyst; wherein the mass ratio of Cu / ZIF, CaS2O3 and PEG is 1:3:5.
[0006] Furthermore, in step 1, the molar ratio of copper ions to zinc ions is 1:4-5; the molar ratio of metal ions to 2-methylimidazole is 0.154-0.2:1; wherein the metal ions are copper ions and zinc ions.
[0007] Furthermore, in step 1, the copper ions and zinc ions as metal sources coordinate with 2-methylimidazole as follows: Dissolve Cu(NO3)2∙3H2O and Zn(NO3)2∙6H2O in solvents to obtain Cu(NO3)2∙3H2O solution and Zn(NO3)2∙6H2O solution respectively; Cu(NO3)2∙3H2O solution and Zn(NO3)2∙6H2O solution were added to 2-methylimidazole solution under stirring conditions; the mixture was fully mixed and reacted; the addition rate of Cu(NO3)2∙3H2O solution and Zn(NO3)2∙6H2O solution was 7 mL / min.
[0008] Furthermore, the stirring speed during the addition of the Cu(NO3)2∙3H2O solution and the Zn(NO3)2∙6H2O solution to the 2-methylimidazole solution was 500-600 r / min; after reacting for 2 h, the rotation speed was adjusted to 200-300 r / min and the reaction was continued for 22 h.
[0009] Further, the replacement reaction process in step 2 is as follows: Add Na2S2O3 solution to the acid solution to fully react; Add CaCl2 to the solution after the reaction and allow it to react sufficiently to obtain CaS2O3; wherein the molar ratio of Na2S2O3 to CaCl2 is 1 to 1.2:1.
[0010] Furthermore, the acid used is hydrochloric acid, and the molar ratio of Na2S2O3 to HCl is 1:1; and the reaction process is maintained in a nitrogen and ice bath environment.
[0011] Further, the reaction process of step 3 is as follows: The Cu / ZIF solution and the CaS2O3 solution were fully stirred and mixed, and then PEG was added and continued to stir. After the reaction was completed, centrifugation was performed at a speed of 11000 rpm for 10 min, and the PEG addition step was repeated. The desired nanocomposite catalyst was obtained after freeze drying.
[0012] An enhanced nanocomposite catalyst based on MOFs material, wherein the nanocomposite catalyst is a mesoporous structure, a metal organic framework structure composed of zinc and copper elements as metal connection points is a skeleton, the surface is coated with PEG, and CaS2O3 is loaded in the mesoporous channels.
[0013] The invention discloses an application of an enhanced nanocomposite catalyst based on MOFs material, and the application of the nanocomposite catalyst in the preparation of chemotherapy drugs for treating tumors.
[0014] Furthermore, the nanocomposite catalyst is used as a tumor-targeted chemotherapy drug carrier.
[0015] The beneficial effects of the present invention are: (1) S2O3 in the nanocomposite catalyst obtained in the present invention 2- It can rapidly enhance the circulation of Cu(II) / Cu(I), maintain a high degradation rate in the pH range of 3.0-10.0, and can play a role in the tumor microenvironment; (2) The nanocomposite catalyst obtained by the present invention can produce ·OH, which can change the cell membrane permeability so that the expression of PMCA, an ion transporter protein in tumor cells, is restricted, thereby preventing Ca 2+ transported out of tumor cells, causing abnormalities in the ion regulation mechanism in tumor cells, leading to intracellular Ca 2+ Excessive accumulation of calcium causes calcium overload, forming a synergistic effect of CDT and calcium death; (2) The nanocomposite catalyst in the present invention is encapsulated by PEG, which reduces its release during transportation and improves the biocompatibility of the nanocomposite catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 These are the SEM and TEM images of the materials obtained in Comparative Examples 1, 3 and Example 1 of the present invention, a is the SEM of the material obtained in Comparative Example 1, b is the SEM of the material obtained in Comparative Example 3, c is the SEM of the catalyst obtained in Example 1, d is the TEM of the catalyst obtained in Example 1, and e is the TEM and elemental mapping of the material obtained in Step 1 of Example 1.
[0017] Figure 2 These are the BET and pore size curves of the materials obtained in Comparative Examples 2 and 3 of the present invention, where a is the result of the material obtained in Comparative Example 2, and b is the result of the material obtained in Comparative Example 3.
[0018] Figure 3 The infrared absorption spectra of the materials and PET obtained in Comparative Examples 1, 2 and Example 1 of the present invention.
[0019] Figure 4 It is the X-ray diffraction spectrum of the materials obtained in Comparative Examples 1, 2, and 3 of the present invention and CaS2O3.
[0020] Figure 5 It is the Zeta potential diagram of the materials obtained in Comparative Examples 1, 2, 3 and Example 1 of the present invention.
[0021] Figure 6 This is the X-ray photoelectron spectrum of the material obtained in Comparative Example 3 of the present invention, a is the full XPS spectrum obtained by Cu / ZIF / Ca measurement, b is the Zn element spectrum, c is the Cu element spectrum, d is the Ca element spectrum, and e is the S element spectrum.
[0022] Figure 7This is the result of cyclic voltammetry measurement after the catalyst Cu / ZIF / Ca obtained in Comparative Example 3 of the present invention reacts with H2O2.
[0023] Figure 8 These are the catalytic performance results of the materials obtained in Comparative Examples 2 and 3 of the present invention, a is the result of Comparative Examples 2 and 3 at a pH of 7.4, b is the result of Comparative Examples 2 and 3 at a pH of 5.0, and c is the result of Comparative Example 3 at different reaction times at a pH of 5.0.
[0024] Fig. 9 It is the UV-visible absorption spectrum of the material obtained in the comparative example of the present invention.
[0025] Fig.10 The materials obtained in each step of Comparative Example 1 and Example 1 of the present invention and the ability of CaS2O3 to generate ·OH, a is the result when pH is 7.4, b is the result when pH is 5.0 and 3% H2O2 exists, Fig.11 These are the fluorescence staining results after co-incubation of tumor cells with the materials obtained in Comparative Examples 1, 2, 3 and Example 1 of the present invention, a is the DCFA-DA fluorescence detection result, b is the C11-BODIPY581 / 589 fluorescence probe detection result, and c is the AM, PI and combined use test results.
[0026] Fig.12 FIG. 1 is a biological transmission electron microscopy image of the catalyst obtained in Example 1 of the present invention after being co-incubated with tumor cells for 12 h, and FIG. b is an enlarged view of FIG. a.
[0027] Fig.13 These are the Alizarin Red S staining results after the materials obtained in Comparative Examples 1, 2, 3 and Example 1 of the present invention were co-incubated with tumor cells for 6 h, where Ⅰ is PBS buffer solution, Ⅱ is Comparative Example 1, Ⅲ is Comparative Example 2, Ⅳ is Comparative Example 3, and Ⅴ is Example 1. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0029] A method for preparing an enhanced nanocomposite catalyst based on MOFs material comprises the following steps: Step 1: Copper ions and zinc ions are used as metal sources to coordinate with 2-methylimidazole, and Cu / ZIF is obtained by centrifugation, washing, and freeze-drying; The specific process is as follows: Dissolve Cu(NO3)2∙3H2O and Zn(NO3)2∙6H2O in methanol and ultrasonically shake until they are completely dissolved to obtain Cu(NO3)2∙3H2O solution and Zn(NO3)2∙6H2O solution; 2-Methylimidazole was dissolved in methanol and ultrasonically vibrated until completely dissolved to obtain a 2-methylimidazole solution, which was placed on a magnetic stirrer; Cu(NO3)2∙3H2O solution and Zn(NO3)2∙6H2O solution were added to the 2-methylimidazole solution at a rate of 7 mL / min, respectively. The solution was stirred at a speed of 600 r / min for 2 h, and the solution gradually changed from light blue to dark blue to obtain a reacted solution. After 2 h, the speed was adjusted to 200-300 r / min and the reaction was continued for 22 h. The product was centrifuged at 11000 rpm for 10 min, washed three times with methanol, washed three times with deionized water, and finally dried under vacuum at 60 °C for 24 h to obtain Cu / ZIF.
[0030] The molar ratio of Zn(NO3)2∙6H2O to Cu(NO3)2∙3H2O is 4-5:1, and the ratio of zinc source to copper source is not less than 4:1. Since copper is difficult to coordinate with 2-methylimidazole, zinc can only be partially replaced by copper with zinc as the skeleton. The organic metal skeleton is difficult to form below this ratio. The molar ratio of the total amount of zinc source and copper source to 2-methylimidazole is 0.154-0.2:1.
[0031] In the above process, the feeding speed needs to be controlled. Too fast a feeding speed can easily lead to cluster formation. Rapid stirring is conducive to the formation of smaller crystal nuclei, so that the final material particle size is smaller.
[0032] Step 2: Thiosulfate and calcium salt undergo replacement reaction to obtain CaS2O3; The reaction process is as follows: Dissolve Na2S2O3 in H2O and completely dissolve it by ultrasonic vibration to obtain Na2S2O3 solution. Add dilute hydrochloric acid to the Na2S2O3 solution and react for 2 hours to obtain the post-reaction solution. During the reaction, nitrogen is always maintained and the environment is ice-water bath. This is because S2O3 2- In a high-temperature air environment, it will decompose into elemental sulfur and sulfur dioxide. Elemental sulfur will usually precipitate out in the form of a yellow solid, while sulfur dioxide will escape in the form of gas, so the external environment needs to be kept stable.
[0033] After the reaction, the solution was filtered and reacted with CaCl2 in a corrosion-resistant reaction vessel for 5 h, and the solution was freeze-dried for 24 h to obtain CaS2O3. The above reaction process was maintained in a nitrogen-freezing and ice-water bath environment throughout the process. This is because the solubility of CaS2O3 can be increased in a low temperature environment.
[0034] Step 3: Fully mix the Cu / ZIF solution obtained in step 1 and the CaS2O3 solution obtained in step 2, add polyethylene glycol PEG and fully mix and react to obtain the desired nanocomposite catalyst; wherein the mass ratio of Cu / ZIF, CaS2O3 and PEG is 1:3:5.
[0035] The specific reaction process is as follows: Cu / ZIF and RO water were mixed and ultrasonically dispersed, and then stirred for 5 min at a speed of 200-300 r / min to obtain a Cu / ZIF solution; the Cu / ZIF solution was placed in a vacuum drying oven and evacuated for 20 min to remove the air in the Cu / ZIF pores; since Cu / ZIF has a large specific surface area and too many pores, the amount of air in it is too high, and vacuuming can extract the air and increase the pressure to make CaS2O3 easier to load.
[0036] 6 g of CaS2O3 was dispersed in 50 mL of water and ultrasonically dispersed for 5 min to obtain a CaS2O3 solution; the vacuumed Cu / ZIF solution and CaS2O3 solution were mixed and stirred at a speed of 300 r / min for 20 min to obtain a mixed solution. 10 g of PEG was added to the mixed solution and mixed and stirred at a speed of 300 r / min for 1 h. Centrifuged at 11000 rpm for 10 min, PEG was added twice, stirred, centrifuged, and freeze-dried to obtain Cu / ZIF / Ca / P. The mass ratio of Cu / ZIF:CaS2O3:PEG was 1:3:5 to ensure the loading of CaS2O3 and the effective encapsulation of PEG.
[0037] Example 1 A method for preparing an enhanced nanocomposite catalyst based on MOFs material comprises the following steps: Step 1: Copper ions and zinc ions are used as metal sources to coordinate with 2-methylimidazole, and Cu / ZIF is obtained by centrifugation, washing, and freeze-drying; 0.25 g of Cu(NO3)2∙3H2O and 1.53 g of Zn(NO3)2∙6H2O were dissolved in 70 mL of methanol respectively and ultrasonically shaken until completely dissolved to obtain solution A and solution B.
[0038] 3.3 g of 2-methylimidazole was dissolved in 70 mL of methanol and ultrasonically vibrated until completely dissolved to obtain solution C, which was then placed on a magnetic stirrer. Solution A and solution B were added to solution C at a rate of 7 mL / min, and the stirrer was kept at a speed of 500 r / min for 2 h. The solution gradually changed from light blue to dark blue, and solution D was obtained.
[0039] After stirring, the speed of the magnetic stirrer was adjusted to 200 r / min, and the reaction was continued for 22 h. The final product was centrifuged at 11000 rpm for 10 min, washed three times with methanol, washed three times with deionized water, and finally dried at 60 °C in vacuum for 24 h to obtain Cu / ZIF.
[0040] Step 2: Thiosulfate and calcium salt undergo replacement reaction to obtain CaS2O3; 3.95 g of Na2S2O3 was dissolved in 46 mL of H2O and ultrasonically vibrated until completely dissolved to obtain solution E. During this process, nitrogen was passed through to deoxygenate and ice-water bath environment was maintained. After Na2S2O3 was completely dissolved, 25 mL of 0.5 mol / L hydrochloric acid solution was added and reacted for 2 h to obtain solution F. Nitrogen was passed through and ice-water bath environment was maintained. After 2 h, the reaction solution was filtered and reacted with 2.7 g of CaCl2 in a corrosion-resistant reaction container for 5 h to obtain solution G. The solution was freeze-dried for 24 h to obtain CaS2O3.
[0041] Step 3: Fully mix the Cu / ZIF solution obtained in step 1 and the CaS2O3 solution obtained in step 2, add polyethylene glycol PEG and fully mix and react to obtain the desired nanocomposite catalyst; wherein the mass ratio of Cu / ZIF, CaS2O3 and PEG is 1:3:5.
[0042] Dissolve 1.5 g of the Cu / ZIF obtained in step 1 in 50 mL of RO water, mix and ultrasonically disperse, and stir at a speed of 300 r / min for 5 min to obtain solution H. Place solution H in a vacuum oven and evacuate for 20 min to remove the air in the pores. Disperse 4.5 g of CaS2O3 in 50 mL of water and ultrasonically disperse for 5 min to obtain solution I. Stir the evacuated solution H and solution I at a speed of 300 r / min for 20 min to obtain solution J.
[0043] 7.5 g of PEG was dissolved in solution J and stirred at 300 r / min for 1 h to obtain solution K. The solution was centrifuged at 11000 rpm for 10 min. After adding PEG twice, the solution was freeze-dried for 24 h to obtain Cu / ZIF / Ca / P (Cu / ZIF-8@CaS2O3@PEG in the figure).
[0044] Example 2 A method for preparing an enhanced nanocomposite catalyst based on MOFs material comprises the following steps: Step 1: Copper ions and zinc ions are used as metal sources to coordinate with 2-methylimidazole, and Cu / ZIF is obtained by centrifugation, washing, and freeze-drying; 0.25 g of Cu(NO3)2∙3H2O and 1.47 g of Zn(NO3)2∙6H2O were dissolved in 60 mL of methanol respectively and ultrasonically shaken until completely dissolved to obtain solution A and solution B.
[0045] 2.9 g of 2-methylimidazole was dissolved in 60 mL of methanol and ultrasonically vibrated until completely dissolved to obtain solution C, which was then placed on a magnetic stirrer. Solution A and solution B were added to solution C at a rate of 7 mL / min, and the stirrer was kept at a speed of 600 r / min for 2 h. The solution gradually changed from light blue to dark blue, and solution D was obtained.
[0046] After stirring, the speed of the magnetic stirrer was adjusted to 200 r / min, and the reaction was continued for 22 h. The final product was centrifuged at 11000 rpm for 10 min, washed three times with methanol, washed three times with deionized water, and finally dried at 60 °C in vacuum for 24 h to obtain Cu / ZIF.
[0047] Step 2: Thiosulfate and calcium salt undergo replacement reaction to obtain CaS2O3; 3.95 g of Na2S2O3 was dissolved in 46 mL of H2O and ultrasonically vibrated until completely dissolved to obtain solution E. During this process, nitrogen was passed through to deoxygenate and ice-water bath environment was maintained. After Na2S2O3 was completely dissolved, 25 mL of 0.5 mol / L hydrochloric acid solution was added and reacted for 2 h to obtain solution F. Nitrogen was passed through and ice-water bath environment was maintained. After 2 h, the reaction solution was filtered and reacted with 2.91 g of CaCl2 in a corrosion-resistant reaction container for 5 h to obtain solution G. The solution was freeze-dried for 24 h to obtain CaS2O3.
[0048] Step 3: Fully mix the Cu / ZIF solution obtained in step 1 and the CaS2O3 solution obtained in step 2, add polyethylene glycol PEG and fully mix and react to obtain the desired nanocomposite catalyst; wherein the mass ratio of Cu / ZIF, CaS2O3 and PEG is 1:3:5.
[0049] Dissolve 1.5 g of the Cu / ZIF obtained in step 1 in 50 mL of RO water, mix and ultrasonically disperse, and stir at a speed of 300 r / min for 5 min to obtain solution H. Place solution H in a vacuum oven and evacuate for 20 min to remove the air in the pores. Disperse 4.5 g of CaS2O3 in 50 mL of water and ultrasonically disperse for 5 min to obtain solution I. Stir the evacuated solution H and solution I at a speed of 300 r / min for 20 min to obtain solution J.
[0050] 7.5 g of PEG was dissolved in J solution and stirred at 300 r / min for 1 h to obtain K solution. The solution was centrifuged at 11000 rpm for 10 min, and PEG was added twice and freeze-dried for 24 h to obtain Cu / ZIF / Ca / P.
[0051] Example 3 A method for preparing an enhanced nanocomposite catalyst based on MOFs material comprises the following steps: Step 1: Copper ions and zinc ions are used as metal sources to coordinate with 2-methylimidazole, and Cu / ZIF is obtained by centrifugation, washing, and freeze-drying; 0.25 g of Cu(NO3)2∙3H2O and 1.43 g of Zn(NO3)2∙6H2O were dissolved in 60 mL of methanol respectively and ultrasonically shaken until completely dissolved to obtain solution A and solution B.
[0052] 2.7 g of 2-methylimidazole was dissolved in 60 mL of methanol and ultrasonically vibrated until completely dissolved to obtain solution C, which was then placed on a magnetic stirrer. Solution A and solution B were added to solution C at a rate of 7 mL / min, and the stirrer was kept at a speed of 600 r / min for 2 h. The solution gradually changed from light blue to dark blue, and solution D was obtained.
[0053] After stirring, the speed of the magnetic stirrer was adjusted to 200 r / min, and the reaction was continued for 22 h. The final product was centrifuged at 11000 rpm for 10 min, washed three times with methanol, washed three times with deionized water, and finally dried at 60 °C in vacuum for 24 h to obtain Cu / ZIF.
[0054] Step 2: Thiosulfate and calcium salt undergo replacement reaction to obtain CaS2O3; Dissolve 3.95 g of Na2S2O3 in 46 mL of H2O and ultrasonically vibrate until completely dissolved to obtain solution E. During this process, nitrogen is passed through to deoxygenate and ice-water bath environment is maintained. After Na2S2O3 is completely dissolved, add 25 mL of 0.5 mol / L hydrochloric acid solution and react for 2 h to obtain solution F. Nitrogen is passed through and ice-water bath environment is maintained. After 2 h, filter the reaction solution and react with 3.05 g of CaCl2 in a corrosion-resistant reaction container for 5 h to obtain solution G. The solution is freeze-dried for 24 h to obtain CaS2O3.
[0055] Step 3: Fully mix the Cu / ZIF solution obtained in step 1 and the CaS2O3 solution obtained in step 2, add polyethylene glycol PEG and fully mix and react to obtain the desired nanocomposite catalyst; wherein the mass ratio of Cu / ZIF, CaS2O3 and PEG is 1:3:5.
[0056] Dissolve 1.5 g of the Cu / ZIF obtained in step 1 in 50 mL of RO water, mix and ultrasonically disperse, and stir at a speed of 300 r / min for 5 min to obtain solution H. Place solution H in a vacuum oven and evacuate for 20 min to remove the air in the pores. Disperse 4.5 g of CaS2O3 in 50 mL of water and ultrasonically disperse for 5 min to obtain solution I. Stir the evacuated solution H and solution I at a speed of 300 r / min for 20 min to obtain solution J.
[0057] 7.5 g of PEG was dissolved in J solution and stirred at 300 r / min for 1 h to obtain K solution. The solution was centrifuged at 11000 rpm for 10 min, and PEG was added twice and freeze-dried for 24 h to obtain Cu / ZIF / Ca / P.
[0058] Example 4 A method for preparing an enhanced nanocomposite catalyst based on MOFs material comprises the following steps: Step 1: Copper ions and zinc ions are used as metal sources to coordinate with 2-methylimidazole, and Cu / ZIF is obtained by centrifugation, washing, and freeze-drying; 0.25 g of Cu(NO3)2∙3H2O and 1.37 g of Zn(NO3)2∙6H2O were dissolved in 60 mL of methanol respectively and ultrasonically shaken until completely dissolved to obtain solution A and solution B.
[0059] 2.4 g of 2-methylimidazole was dissolved in 70 mL of methanol and ultrasonically vibrated until completely dissolved to obtain solution C, which was then placed on a magnetic stirrer. Solution A and solution B were added to solution C at a rate of 7 mL / min, and the stirrer was kept at a speed of 600 r / min for 2 h. The solution gradually changed from light blue to dark blue, and solution D was obtained.
[0060] After stirring, the speed of the magnetic stirrer was adjusted to 200 r / min, and the reaction was continued for 22 h. The final product was centrifuged at 11000 rpm for 10 min, washed three times with methanol, washed three times with deionized water, and finally dried at 60 °C in vacuum for 24 h to obtain Cu / ZIF.
[0061] Step 2: Thiosulfate and calcium salt undergo replacement reaction to obtain CaS2O3; 3.16 g of Na2S2O3 was dissolved in 46 mL of H2O and ultrasonically vibrated until completely dissolved to obtain solution E. During this process, nitrogen was passed through to deoxygenate and ice-water bath environment was maintained. After Na2S2O3 was completely dissolved, 25 mL of 0.4 mol / L hydrochloric acid solution was added and reacted for 2 h to obtain solution F. Nitrogen was passed through and ice-water bath environment was maintained. After 2 h, the reaction solution was filtered and reacted with 2.55 g of CaCl2 in a corrosion-resistant reaction container for 5 h to obtain solution G. The solution was freeze-dried for 24 h to obtain CaS2O3.
[0062] Step 3: Fully mix the Cu / ZIF solution obtained in step 1 and the CaS2O3 solution obtained in step 2, add polyethylene glycol PEG and fully mix and react to obtain the desired nanocomposite catalyst; wherein the mass ratio of Cu / ZIF, CaS2O3 and PEG is 1:3:5.
[0063] Dissolve 2 g of Cu / ZIF obtained in step 1 in 50 mL of RO water, mix and ultrasonically disperse, and stir at a speed of 300 r / min for 5 min to obtain H solution. Place H solution in a vacuum drying oven and evacuate for 20 min to remove the air in the pores. Disperse 6 g of CaS2O3 in 50 mL of water and ultrasonically disperse for 5 min to obtain I solution. Stir the vacuumized H solution and I solution at a speed of 300 r / min for 20 min to obtain J solution.
[0064] 10 g of PEG was dissolved in solution J and stirred at 300 r / min for 1 h to obtain solution K. The solution K was centrifuged at 11000 rpm for 10 min. After adding PEG twice, the solution was freeze-dried for 24 h to obtain Cu / ZIF / Ca / P.
[0065] Example 5 A method for preparing an enhanced nanocomposite catalyst based on MOFs material comprises the following steps: Step 1: Copper ions and zinc ions are used as metal sources to coordinate with 2-methylimidazole, and Cu / ZIF is obtained by centrifugation, washing, and freeze-drying; 0.2 g of Cu(NO3)2∙3H2O and 1.02 g of Zn(NO3)2∙6H2O were dissolved in 60 mL of methanol respectively and ultrasonically shaken until completely dissolved to obtain solution A and solution B.
[0066] 1.7 g of 2-methylimidazole was dissolved in 60 mL of methanol and ultrasonically vibrated until completely dissolved to obtain solution C, which was then placed on a magnetic stirrer. Solution A and solution B were added to solution C at a rate of 7 mL / min, and the stirrer was kept at a speed of 600 r / min for 2 h. The solution gradually changed from light blue to dark blue, and solution D was obtained.
[0067] After stirring, the speed of the magnetic stirrer was adjusted to 200 r / min, and the reaction was continued for 22 h. The final product was centrifuged at 11000 rpm for 10 min, washed three times with methanol, washed three times with deionized water, and finally dried at 60 °C in vacuum for 24 h to obtain Cu / ZIF.
[0068] Step 2: Thiosulfate and calcium salt undergo replacement reaction to obtain CaS2O3; 3.16 g of Na2S2O3 was dissolved in 47 mL of H2O and ultrasonically vibrated until completely dissolved to obtain solution E. During this process, nitrogen was passed through to deoxygenate and ice-water bath environment was maintained. After Na2S2O3 was completely dissolved, 25 mL of 0.4 mol / L hydrochloric acid solution was added and reacted for 2 h to obtain solution F. Nitrogen was passed through and ice-water bath environment was maintained. After 2 h, the reaction solution was filtered and reacted with 2.66 g of CaCl2 in a corrosion-resistant reaction container for 5 h to obtain solution G. The solution was freeze-dried for 24 h to obtain CaS2O3.
[0069] Step 3: Fully mix the Cu / ZIF solution obtained in step 1 and the CaS2O3 solution obtained in step 2, add polyethylene glycol PEG and fully mix and react to obtain the desired nanocomposite catalyst; wherein the mass ratio of Cu / ZIF, CaS2O3 and PEG is 1:3:5.
[0070] Dissolve 2 g of Cu / ZIF obtained in step 1 in 50 mL of RO water, mix and ultrasonically disperse, and stir at a speed of 300 r / min for 5 min to obtain H solution. Place H solution in a vacuum drying oven and evacuate for 20 min to remove the air in the pores. Disperse 6 g of CaS2O3 in 50 mL of water and ultrasonically disperse for 5 min to obtain I solution. Stir the vacuumized H solution and I solution at a speed of 300 r / min for 20 min to obtain J solution.
[0071] 10 g of PEG was dissolved in solution J and stirred at 300 r / min for 1 h to obtain solution K. The solution K was centrifuged at 11000 rpm for 10 min. After adding PEG twice, the solution was freeze-dried for 24 h to obtain Cu / ZIF / Ca / P.
[0072] Comparative Example 1 In order to illustrate the beneficial effects of the present invention, a comparative example is set, with ZIF-8MOF material as a comparison, and the specific preparation method is as follows: 1.5 g of zinc nitrate hexahydrate was dissolved in 70 mL of methanol and ultrasonically dispersed until completely dissolved to obtain solution L. In addition, 3.3 g of 2-methylimidazole was dissolved in 70 mL of methanol and ultrasonically dispersed until completely dissolved to obtain solution M. The L solution was slowly added into the M solution and turned milky white. After stirring at 500 r / min at room temperature for 2 h, the speed was adjusted to 200 r / min and the reaction was continued for 22 h. Finally, it was centrifuged and washed three times with methanol and water, and dried in a vacuum at 60 °C for 12 h to obtain ZIF-8.
[0073] Comparative Example 2 The comparative example preparation method is as follows: 0.3 g of Cu(NO3)2∙3H2O and 1.91 g of Zn(NO3)2∙6H2O were dissolved in 70 mL of methanol respectively and ultrasonically shaken until completely dissolved to obtain solution A and solution B.
[0074] 3.06 g of 2-methylimidazole was dissolved in 70 mL of methanol and ultrasonically vibrated until completely dissolved to obtain solution C, which was then placed on a magnetic stirrer. Solution A and solution B were added to solution C at a rate of 7 mL / min, and the stirrer was kept at a speed of 500 r / min for 2 h. The solution gradually changed from light blue to dark blue, and solution D was obtained.
[0075] After stirring, the speed of the magnetic stirrer was adjusted to 200 r / min, and the reaction was continued for 22 h. The final product was centrifuged at 11000 rpm for 10 min, washed three times with methanol, washed three times with deionized water, and finally dried at 60 °C in vacuum for 24 h to obtain Cu / ZIF (Cu / ZIF-8).
[0076] Comparative Example 3 The comparative example preparation method is as follows: Dissolve 5 g of Na2S2O3 in 45 mL of H2O and ultrasonically vibrate until completely dissolved to obtain solution E. During this process, nitrogen is passed through to deoxygenate and ice-water bath environment is maintained. After Na2S2O3 is completely dissolved, add 25 mL of 0.5 mol / L hydrochloric acid solution and react for 2 h to obtain solution F. Nitrogen is passed through and ice-water bath environment is maintained. After 2 h, filter the reaction solution and react with 2.7 g of CaCl2 in a corrosion-resistant reaction container for 5 h to obtain solution G. The solution is freeze-dried for 24 h to obtain CaS2O3.
[0077] 2 g of Cu / ZIF obtained in Example 1 was dissolved in 50 mL of RO water, mixed and ultrasonically dispersed, and stirred at a speed of 300 r / min for 5 min to obtain H solution. The H solution was placed in a vacuum drying oven and evacuated for 20 min to remove the air in the pores. 4 g of CaS2O3 was dispersed in 50 mL of water and ultrasonically dispersed for 5 min to obtain I solution. The vacuumized H solution and I solution were stirred at a speed of 300 r / min for 20 min to obtain J solution. After centrifugation at a speed of 11000 rpm for 10 min, the solid was freeze-dried for 24 h to obtain Cu / ZIF / Ca (Cu / ZIF-8@CaS2O3).
[0078] The effects of the present invention are described below through test results.
[0079] Figure 1 The SEM and TME images of the materials obtained in the comparative example and embodiment 1 are shown in FIG. Figure 1 It can be seen that the ZIF-8 obtained in Comparative Example 1 has a relatively clear regular dodecahedron structure and is suitable for a series of applications such as energy storage and drug delivery. Figure 1 As can be seen in b, the morphology of Cu / ZIF / Ca after loading with CaS2O3 does not change significantly. Figure 1 As can be seen in Figure c, the surface roughness of Cu / ZIF / Ca / P increases after being coated with PEG. Figure 1 As can be seen in figure d, Cu / ZIF / Ca / P has a loading of CaS2O3. From its elemental mapping diagram, it can be seen that Cu / ZIF is a metal organic framework structure with zinc and copper elements as metal connection points.
[0080] Figure 2 The BET and pore size curves of Comparative Examples 2 and 3. It can be seen from the figure that the specific surface area of Cu / ZIF without CaS2O3 loading reaches 1354 m 2 / g, and the specific surface area of Cu / ZIF / Ca after CaS2O3 loading is 310 m 2 / g. From the results, it can be seen that CaS2O3 is effectively loaded in Cu / ZIF.
[0081] Figure 3 The infrared absorption spectra of Comparative Examples 1 and 2 and Example 1 and PEG are shown in the figure. It can be seen from the figure that the infrared spectra of ZIF-8, Cu / ZIF, and Cu / ZIF / Ca / P are basically the same, with 1584 cm -1 The stretching vibration of C=N group is at 1251 cm -1 ) and CH(2876 cm -1) Two characteristic peaks indicate the successful encapsulation of PEG.
[0082] Figure 4 The X-ray diffraction spectra of Comparative Examples 1, 2, 3 and CaS2O3 (prepared by the method of step 2 of any embodiment) are shown in the figure. It can be seen from the figure that the crystal structure of Cu / ZIF and Cu / ZIF / Ca is basically the same as ZIF-8, and the characteristic absorption peak intensity of Cu / ZIF is much higher than that of ZIF-8, which proves that the crystallinity of Cu / ZIF is higher than that of ZIF-8, while the characteristic absorption peak intensity of Cu / ZIF / Ca is much lower, indicating that the crystallinity is lowered, which is caused by the fact that some CaS2O3 remains on the surface of Cu / ZIF. At the same time, the characteristic peak of CaS2O3 is detected in Cu / ZIF / Ca, which proves the successful loading of CaS2O3.
[0083] Figure 5 The Zeta potential diagram of the materials obtained in Comparative Examples 1, 2, 3 and Example 1 shows that due to the addition of excess 2-methylimidazole when preparing the MOF material, its strong electronegativity and the coordination of zinc and copper present a higher potential. The encapsulation of PEG greatly reduces the potential of Cu / ZIF / Ca / P, and the negative potential can promote the circulation of nanomaterials in the blood, making the nanomaterials more efficient in entering tumor cells.
[0084] Figure 6 The X-ray photoelectron spectrum of the material obtained in Comparative Example 3 shows that the peaks of Zn, Cu, Ca, O, C, N, and S appear in the spectrum of Cu / ZIF / Ca, and the peaks of Zn 2p appear in the spectrum of Zn 2+ (1021.78, 1044.63eV) and Cu 2+ The signal peaks of (932.48, 952.13 eV) indicate that the valence state of Zn and Cu elements in Cu / ZIF is in a divalent state. The two characteristic peaks of Ca 2p at 347.08 eV and 350.73 eV and the two characteristic peaks of S 2p at 163.58 eV and 167.28 eV confirm the existence of CaS2O3. Compared with the TEM image, it is proved that CaS2O3 exists on the surface and inside of Cu / ZIF.
[0085] Figure 7 Cyclic voltammetry measurement of Cu / ZIF and S2O3 2- The reaction image of H2O2 shows that in the absence of glutathione, the Cu + With Cu 2+ A good cycle can be achieved, proving that S2O3 2- Enhanced success of Fenton-like reactions.
[0086] Figure 8 The catalytic performance results of Comparative Examples 1 and 3 are ESR tests of Cu / ZIF and Cu / ZIF / Ca in the presence of H2O2 and under different pH and time conditions. As can be seen from the figure, a is that there is no ∙OH signal in Cu / ZIF within 0-5min, proving that Cu / ZIF in this environment cannot catalyze H2O2 to produce ∙OH. Under the condition of pH 7.4, Cu / ZIF / Ca produced a relatively strong 1:2:2:1 characteristic peak within 0-5min, which is a unique signal after ∙OH combines with 5,5-dimethyl-1-pyrroline-N-oxide (DMPO).
[0087] from Figure 8 As can be seen in Figure b, the signal peak generated by Cu / ZIF in 0-5min is higher than that of Cu / ZIF / Ca, which may be due to the presence of Cu(Ⅲ) which hinders the binding of DMPO with ∙OH. Figure 8 As can be seen in Figure c, under pH 5.0, the signal peak of ∙OH generated by adding Cu / ZIF / Ca within 0-20 min first increased and then decreased, which proves that the binding of DMPO with ∙OH is hindered. In order to further verify Cu(Ⅲ), periodate was used as a scavenger for Cu(Ⅲ), making it show an ultraviolet absorption peak at 340nm.
[0088] Fig. 9 This is the capture of Cu(Ⅲ) under the conditions of pH 5.0 and the presence of H2O2. As can be seen from the figure, Cu / ZIF does not cause changes in the peak shape at 340nm. After the addition of CaS2O3, a more obvious red shift occurs, proving the possibility of the existence of Cu(Ⅲ).
[0089] Fig.10 is the ability of the nanocatalyst to generate ·OH under different pH conditions. 3'3'5'5'-tetramethylbenzidine (TMB) was used to react with comparative examples 1, 2, and 3. TMB is colorless and transparent when dissolved in DMSO. Strong oxidizing ROS can oxidize TMB to generate a group with a blue conjugated structure. Its unique absorption peak at 652 nm can be detected using an ultraviolet spectrophotometer (UV-vis). Fig.10 In a, Cu / ZIF / Ca, Cu / ZIF, CaS2O3, and ZIF-8 at a concentration of 200 µg / mL were added to a 3% H2O2 solution to detect their absorption peaks at 650 nm. The results showed that only Cu / ZIF / Ca could make TMB produce a strong peak at 650 nm, which is the same as the ESR test results, proving that S2O3 2- It can expand the pH limit range of Fenton-like reactions. Fig.10Figure b shows that under the condition of pH 5.0 and 3% H2O2, 100 µg / mL of Cu / ZIF / Ca, Cu / ZIF, CaS2O3, and ZIF-8 were added respectively. The results show that the ∙OH signal peak generated by Cu / ZIF / Ca is higher than that of Cu / ZIF, which further proves that S2O3 2- Effect as an enhancer of Fenton-like reactions.
[0090] In order to illustrate the effect of the catalyst obtained by the present invention on tumors, the materials obtained in Comparative Examples 1, 2, 3 and Example 1 were co-incubated with tumor cells for 6 h, and DCFH-DA was used to detect reactive oxygen species (ROS) and nitric oxide (NO) and determine the overall degree of oxidative stress. The intracellular ∙OH can oxidize non-fluorescent DCFH to generate fluorescent DCF. The results are shown in FIG. Fig.11 shown. Fig.11 Figure a is the test result of the DCFA-DA probe. It can be seen that when the concentration of Cu / ZIF / Ca / P is 50 µg / mL, the most ROS can be detected, proving that the catalyst obtained in the present invention has a relatively good catalytic effect.
[0091] Fig.11 Figure b is the test result of C11-BODIPY581 / 589 ratio fluorescence probe. From the figure, we can see that the fluorescence changes of LPO membranes stimulated by different materials can be detected to detect the fluorescence of LPO membranes and the effect of lipid peroxidation. Similarly, more fluorescence can be detected in the Cu / ZIF / Ca / P group, which indicates that more ∙OH can be produced in the Cu / ZIF / Ca / P group to oxidize the cell membrane and make it show corresponding fluorescence changes. Fig.11 Figure c is the test result of AM, PI and their combination, because the combination can only pass through the disordered area of the dead cell membrane to reach the cell nucleus, embed into the DNA double helix area of the cell, and produce fluorescence, only staining dead cells, which can more intuitively show the killing ability of the material on tumor cells. It can be seen from the figure that Cu / ZIF, Cu / ZIF / Ca, Cu / ZIF / Ca / P can cause tumor cell death, and there are almost no living cells in Cu / ZIF / Ca and Cu / ZIF / Ca / P, indicating that the encapsulation of CaS2O3 and PEG can increase the catalytic effect and drug encapsulation rate of the nanocatalyst to a greater extent.
[0092] Fig.12 This is a biological transmission electron microscope image of the catalyst obtained in Example 1 of the present invention after co-incubation with tumor cells for 12 hours. It can be seen from the figure that the cell morphology is obviously abnormal; most mitochondria in the cytoplasm have swollen, and the mitochondria are round, oval or long strips, the cristae structure is dissolved and broken, the matrix is lost, local vacuolation occurs, and the outer membrane is continuous and intact; the rough endoplasmic reticulum is expanded. This is due to the Zn 2+Ion disorder and Ca in tumor cells 2+ Caused by overloading.
[0093] Fig.13 The Alizarin Red S staining images after co-incubation with tumor cells in Comparative Examples 1, 2, 3 and Example 1 of the present invention are shown. The Alizarin Red S calcium staining method is an authoritative and classic technical method that aims to analyze the orange-red calcium deposition phenomenon in fixed cell samples by using chelation technology to produce a complex between calcium ions and Alizarin Red S. As can be seen from the figure, orange-red calcium deposition appears in Cu / ZIF / Ca and Cu / ZIF / Ca / P, proving that Ca 2+ Successfully distributed in tumor cells.
[0094] The Cu / ZIF / Ca / P prepared by the present invention can be used as a carrier to load other chemotherapeutic drugs, and can also be directly used as a chemotherapeutic drug.
[0095] The present invention uses PEG to wrap Cu / ZIF and loads CaS2O3 to obtain Cu / ZIF / Ca / P. The Cu / ZIF prepared by the present invention is a nanocarrier with small particle size, large specific surface area and high crystallinity. The introduction of CaS2O3 can greatly enhance the efficiency of chemodynamic therapy on the one hand, and produce excessive ∙OH on the other hand to inhibit Ca 2+ The expression of efflux proteins also causes mitochondrial calcium overload in tumor cells, which in turn promotes apoptosis of cancer cells through oxidative stress. The use of bimetallic zinc and copper to co-construct an organic metal framework and load CaS2O3 to enhance chemodynamic therapy and calcium death synergistic therapy provides a new construction idea and treatment model for the design and biomedical application of new nanocatalysts.
Claims
1. A method for preparing an enhanced nanocomposite catalyst based on MOFs material, characterized in that: The following steps are involved: Step 1: Copper ions and zinc ions are used as metal sources to coordinate with 2-methylimidazole, and Cu / ZIF is obtained by centrifugation, washing, and freeze-drying; Step 2: Thiosulfate and calcium salt undergo replacement reaction to obtain CaS2O3; Step 3: Fully mix the Cu / ZIF solution obtained in step 1 and the CaS2O3 solution obtained in step 2, add polyethylene glycol PEG and fully mix and react to obtain the desired nanocomposite catalyst; wherein the mass ratio of Cu / ZIF, CaS2O3 and PEG is 1:3:
5.
2. The method for preparing an enhanced nanocomposite catalyst based on MOFs material according to claim 1, characterized in that: In the step 1, the molar ratio of copper ions to zinc ions is 1:4-5; the molar ratio of metal ions to 2-methylimidazole is 0.154-0.2:1; wherein the metal ions are copper ions and zinc ions.
3. The method for preparing an enhanced nanocomposite catalyst based on MOFs material according to claim 1, characterized in that: In the step 1, the coordination process of copper ions and zinc ions as metal sources with 2-methylimidazole is as follows: Dissolve Cu(NO3)2∙3H2O and Zn(NO3)2∙6H2O in solvents to obtain Cu(NO3)2∙3H2O solution and Zn(NO3)2∙6H2O solution respectively; Cu(NO3)2∙3H2O solution and Zn(NO3)2∙6H2O solution were added to 2-methylimidazole solution under stirring conditions; the mixture was fully mixed and reacted; the addition rate of Cu(NO3)2∙3H2O solution and Zn(NO3)2∙6H2O solution was 7 mL / min.
4. The method for preparing an enhanced nanocomposite catalyst based on MOFs material according to claim 3, characterized in that: The stirring speed during the addition of the Cu(NO3)2∙3H2O solution and the Zn(NO3)2∙6H2O solution to the 2-methylimidazole solution is 500-600 r / min; after reacting for 2 h, the rotation speed is adjusted to 200-300 r / min and the reaction is continued for 22 h.
5. The method for preparing an enhanced nanocomposite catalyst based on MOFs material according to claim 1, characterized in that: The replacement reaction process in step 2 is as follows: Add Na2S2O3 solution to the acid solution to fully react; Add CaCl2 to the solution after the reaction and allow it to react sufficiently to obtain CaS2O3; wherein the molar ratio of Na2S2O3 to CaCl2 is 1 to 1.2:
1.
6. The method for preparing an enhanced nanocomposite catalyst based on MOFs material according to claim 5, characterized in that: The acid used was hydrochloric acid, and the molar ratio of Na2S2O3 to HCl was 1:1; the reaction process was maintained in a nitrogen-filled and ice-bath environment.
7. The method for preparing an enhanced nanocomposite catalyst based on MOFs material according to claim 1, characterized in that: The reaction process of step 3 is as follows: The Cu / ZIF solution and the CaS2O3 solution were fully stirred and mixed, and then PEG was added and continued to stir. After the reaction was completed, centrifugation was performed at a speed of 11000 rpm for 10 min, and the PEG addition step was repeated. The desired nanocomposite catalyst was obtained after freeze drying.
8. The enhanced nanocomposite catalyst based on MOFs material obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The nano composite catalyst is a mesoporous structure, the metal organic framework structure formed by zinc and copper elements as metal connection points is the skeleton, the surface is wrapped by PEG, and CaS2O3 is loaded in the mesoporous channels.
9. The use of the enhanced nanocomposite catalyst based on MOFs material as claimed in claim 8, characterized in that: The nano composite catalyst is used in the preparation of chemotherapy drugs for treating tumors.
10. The use of the enhanced nanocomposite catalyst based on MOFs material according to claim 9, characterized in that: The nano composite catalyst is used as a tumor-targeted chemotherapy drug carrier.
Citation Information
Patent Citations
Preparation method of MOFs nano material supporting nano metal particles
CN108097316A
Preparation method of composite photocatalytic material of Fe3O4-N doped with Ni / Zn-MOFs / g-C3N4
CN108579819A
Preparation method of TiO2 / ZIF-8 composite photocatalyst
CN109499620A
Preparation method of long-circulation multifunctional metal organic framework nano preparation
CN114732795A
Preparation method and application of copper-doped ZIF-8 nano composite material
CN118340909A
Cited By
Copper death nanometer material for radiotherapy sensitization and application of copper death nanometer material
CN120586054A
